EFFECT OF POX VACCINE ON BLOOD PICTURE IN ADULT EWES - Ibraheem Ahmad Noah; Suha A. Rasheed (Basrah Journal of Veterinary Research)
Sheep pox is an enzootic disease in Iraq and the regional countries. A huge amount of money eitherspent on vaccines or lost due to the morbidities every year. For unknown reason, sometimes vaccinationis not efficient enough to provide the required protection. We conducted this study to investigate theeffect of the most popular pox vaccine on some physiological parameters, which may reflect anyadverse effect on the body. We used twelve adult ewes, divided into two groups (6/each); the first groupis the control, injected with normal saline (0.9% NaCl) intradermal, whereas the vaccine was injectedsimilarly in the animals of the other group. Blood samples were obtained weekly before and after thetreatment onset. Results revealed that there are changes in blood count parameters, starting from thevaccination time (the second week). Interestingly, RBC count was decreased just after the vaccination,whereas, a significant (p≤ 0.05) decreased in the WBC was also observed, with consequent significantchanges in the differential leukocytes count (DLC), These changes were accompanied with signs of reelevationafter two weeks of vaccination. In conclusion, there are unexpected changes in the RBC countresult from pox vaccination. Furthermore, the developing of immunity starts with a decrease in theWBCs, which needs more than two weeks to restore the normal value.